Eksperimentalno preskušanje prenosa toplote v Lorenzovem postopku z uporabo zeotropnih zmesi - Soldo, Vladimir (Strojniški vestnik, 2003)
A comparison has been made between the thermodynamic efficiency of a single-component refrigerent R22 and a substitute zeotropic mixture R407C in a system operating under the same conditions. The construction of a refrigerating system that uses R22 and R407C is presented, along with measurements of all the relevant data (temperature, pressure and flow rate). their acquisition, and their analysis. Our results show that the refrigerant R407C is a good substitute for the refrigerant R22 at higher evaporation temperatures. Although the theoretical results suggest that R407C will increase efficiency compared to R22, the experimental results did not confirm it. This because in the process with the refrigerant R407C the heat-transfer coefficients are lower.
Keywords: zmesi zeotropske; procesi Lorentz; izkoristki termodinamični; prenos toplote; hladilni sistemi; Lorenzov postopek; hladiva